Fluid Bolus Therapy in Pediatric Sepsis: Current Knowledge and Future Direction - Gelbart, Ben (Frontiers in Pediatrics, 2018)
Sepsis is a leading cause of morbidity and mortality in children with a worldwide prevalence in paediatric intensive care units of approximately 8%. Fluid bolus therapy (FBT) is a first line therapy for resuscitation of septic shock and has been a recommendation of international guidelines for nearly two decades. The evidence base supporting these guidelines are based on limited data including animal studies and case control studies. In recent times, evidence suggesting harm from fluid in terms of morbidity and mortality have generated interest in evaluating FBT. In view of this, studies of fluid restrictive strategies in adults and children have emerged. The complexity of studying FBT relates to several points. Firstly, the physiological and haemodynamic response to FBT including magnitude and duration is not well described in children. Secondly, assessment of the circulation is based on non-specific clinical signs and limited haemodynamic monitoring with limited physiological targets. Thirdly, FBT exists in a complex myriad of pathophysiological responses to sepsis and other confounding therapies. Despite this, a greater understanding of the role of FBT in terms of the physiological response and possible harm is warranted. This review outlines current knowledge and future direction for FBT in sepsis.